The issue of literary norms in the language of cinema - Shirinova, Mexrigiyo (FILOLOGIYA UFQLARI JURNALI, 2024)
The article considers some aspects of cinema art that differ from other forms of art, the concept of "language of cinema" and its features, literary norms, and the names of films. The following features of the language of cinema are listed: audio-visuality, mobility, imagery, expressiveness, communicativeness, entertainment, personality for the screen, sociality, simplicity, attractiveness, understanding. It is argued that the creation of a film corresponding to our time is directly related to the analysis of the language of cinema in a linguistic aspect. And also, some deviations from literary norms in the names of Uzbek films in the period of independence have been clarified. The spelling, punctuation, morphological, and stylistic deviations in the names of films are analyzed.